Evaluating model and simulation analyzing for P2P Churn - YANG Dong; DONG Ping; ZHANG Hong-ke (Tongxin xuebao)
Most P2P algorithms based on distributed Hash table（DHT） faced Churn,which was caused by the continuous process of node joining and failure.A Churn evaluating model was proposed and its formulized description,which could give some important instructions for analyzing current P2P algorithms and designing new algorithms.Using this model,a simulation including three P2P algorithm Chord,Kelips,and Tapestry was done.The experiment results show the capability of these algorithms under Churn,the advantage of Chord than others,and the most important factor affecting Churn.